2013
DOI: 10.5812/ircmj.11810
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers Affecting Access to Preventive Dental Services: Application of DEMATEL Method

Abstract: BackgroundIdentifying perceived access barriers to preventive dental services is one of the basic steps to improve the public health.ObjectivesThis study aimed to determine the perceived barriers affecting access to preventive dental services in one of Tehran dental clinics in 2012.Patients and MethodsThis research was a cross-sectional descriptive-analytical study conducted in one of Tehran dental clinics in 2012 using decision–making trial and evaluation laboratory (DEMATEL) method. The study sample included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
4
33
0
5
Order By: Relevance
“…Patients often stress that they are too high and the treatment should be financed by insurance benefits. Nevertheless, more than half of respondents is willing to pay a higher amount to avoid tooth loss, similarly as in the research of Bahadori et al [14].…”
Section: Discussionmentioning
confidence: 62%
“…Patients often stress that they are too high and the treatment should be financed by insurance benefits. Nevertheless, more than half of respondents is willing to pay a higher amount to avoid tooth loss, similarly as in the research of Bahadori et al [14].…”
Section: Discussionmentioning
confidence: 62%
“…Cost is an important factor in patients' treatment choices and it can create a barrier to receiving dental care (20). Other studies have also concluded that more than half of the respondents were willing to pay a greater amount in order to avoid tooth extraction (16,23). However, it is not known whether their concerns about costs were a general concern about the cost of treatment rather than a specific concern about the cost of treatment for that specific tooth.…”
Section: Patient Concernsmentioning
confidence: 99%
“…Knowledge on factors affecting dental health‐care utilisation is important to inform the health system and develop policies aimed at improving dental health‐care services, service utilisation and oral health status of people. However, several factors, including economic status, age, gender, educational level and individual's perspective on dental hygiene, affect dental health‐care. Generally, two categories of variables affect dental health‐care utilisation.…”
Section: Introductionmentioning
confidence: 99%